The Interactive Kahoot Game's Impact on Student Interest and Learning Independence in Mathematics Learning - Indah Kusuma Wardani; Sucipto; Nuril Huda; Sunardjo (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2026)
This study aims to examine the impact of the interactive game-based platform Kahoot on student engagement and learning independence in mathematics instruction at Kebun 2 Elementary School. The study addresses two critical issues: low levels of student engagement and the limited development of independent learning strategies in mastering mathematical concepts, both of which necessitate the adoption of innovative pedagogical approaches to foster active participation. This research offers a novel contribution by exploring the application of Kahoot as an interactive instructional tool in elementary mathematics education within a local context, where such studies remain limited. A quasi-experimental design with a quantitative approach was employed, involving 50 fifth-grade students (classes V-A and V-B) selected through saturation sampling. Data were collected using a structured questionnaire measuring student engagement and learning independence. Statistical analysis was conducted using the Independent Samples t-test with IBM SPSS version 27. The findings reveal that the post-test results for both variables yielded a p-value of 0.000, which is below the established threshold of α = 0.05, indicating a statistically significant difference between the experimental and control groups. These results demonstrate that the integration of Kahoot significantly enhances student engagement and promotes greater learning independence in mathematics. In conclusion, this study underscores the pedagogical value of interactive digital platforms as effective alternative strategies for creating more engaging learning environments and fostering student autonomy in elementary mathematics education